Factors Associated with Clinician Adherence to USPSTF Diabetes Screening Recommendations - Elaine Seaton Banerjee; Kyle Shaak; Nicole Burgess; Melanie Johnson; Beth Careyva (SAGE Publishing, 2021)
Introduction/Objectives: Diabetes and prediabetes impact nearly half of the US adult population and are associated with significant health risks but may be underdiagnosed. Effective screening may improve diagnosis and give patients opportunity to manage their disease. The purpose of this study was to determine screening rates, identify characteristics predictive of screening, and evaluate correct diagnosis of diabetes and prediabetes. Methods: Retrospective chart review of 71 433 patients eligible for diabetes screening, defined by completing A1c test within the 3-year study period. Results: A total of 31.3% of eligible patients received diabetes screening. Factors associated with screening include older age, female sex, non-white race, Hispanic ethnicity, Medicare or Medicaid insurance, higher BMI, and having a medical comorbidity. History of prediabetes or gestational diabetes were the strongest predictors for diabetes screening, but history of gestational diabetes was under-documented. Of those screened, 10.4% had a result consistent with diabetes and 51.8% had a result consistent with prediabetes. However, 52.9% of these patients had a missed diagnosis. Conclusions: Findings of this study indicate the need for uniform coverage for diabetes screening for all insurances, increased documentation of gestational diabetes to improve screening for patients with this history, and improving accurate diagnosis after screening is completed.